IMPLEMENTASI PROGRAM DETEKSI DINI KANKER SERVIKS MELALUI IVA TEST DI DINAS KESEHATAN KABUPATEN SUKOHARJO - Afifah Faza Nidar (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
Early detection program for cervical cancer through IVA test carried out by the Sukoharjo Regency Health Department has not reached the target set by the government of 1.8% in 2022 from the 10% target set. Positive IVA results in Sukoharjo in 2021 were the third highest in Central Java at 11.58%. The aim of the research is to determine the implementation of the early detection program for cervical cancer through the IVA test at the Sukoharjo Regency Health Department. This type of qualitative research uses a descriptive approach using in-depth interviews and observation. The subjects of this research were 4 informants. Triangulation uses triangulation of sources, namely the head of health services, disease prevention and control. The instruments in this research were researchers, in-depth interview guidelines and observation guidelines. The research results show that the implementation of early detection program for cervical cancer through IVA at Sukoharjo Regency Health Department is not optimal. The input aspect components which include regulations and guidelines, information systems and resources are in accordance with regulations, while for implementing staff there are still several public health centers that do not have trained doctors and there is one community health center that cannot carry out cryotherapy. The process components which include promotion are in accordance with regulations, socialization is not evenly distributed and the material has not been fully delivered, early detection and screening have been carried out in accordance with guidelines but postexamination counseling has not been carried out. The output component which includes the morbidity rate due to cancer will still continue to increase if this examination is not carried out and the coverage of early detection of cervical cancer has not yet met the set targets. The advice for the Health Service and community health centers is to continue checking and supervising socialization in order to achieve the expected targets.